Description of Covid-19 Patients at Bhakti Dharma Husada Surabaya Hospital in February 2022 - Yunika Trisnawati (Jurnal Biosains Pascasarjana, 2022)
Indonesia were entering the third wave of COVID-19 starting in January 2022, where there has been an increase in COVID-19 cases. Bhakti Dharma Husada Hospital Surabaya began to experience an increase in COVID- 19 inpatients in February 2022. This study aims to describe COVID-19 cases treated at Bhakti Dharma Husada Hospital according to gender, age, vaccination status, and severity level.. This research is a descriptive observational study with a case series approach. The data source in this study was secondary data taken from the online hospital application of the Directorate General of Health and Safety in February 2022. The majority of COVID-19 patients treated at the Bhakti Dharma Husada Hospital in February 2022 were female ; 87 (50,6%), the most age of patients were 51-60 years old ; 35 (20,4 %), most had a history of no vaccine ; 82 (47,7%), and the majority of the severity level was mild 132 (76,7%).